Prooxidant - Antioxidant Balance In CAD Patients - F Nabatchian; N Einollahi; N Dashti; F Sarrafnejad; GHR Vatani (پیاورد سلامت, 2011)
Background and Aim: The balance between ROS generation and antioxidant activity is critical to the pathogenesis of oxidative stress related disorders. In this study the prooxidant - antioxidant balance and its correlation with lipid profile and uric acid was determined to evaluate the PAB as a prognostic factor for CAD.Materials and Methods: Seventy - two patients and sixty eight healthy volunteers were enrolled in this study. The values of PAB were determined by using standard solutions and ELISA method. Triglyceride, total cholesterol, LDL- cholesterol, HDL - cholesterol and uric acid were measured by enzymatic method.Results: The PAB values of CAD patients and control group were 70.01±3.36 (HK unit) and 66.40 ± 2.84 (HK unit) respectively. There was no significant difference between PAB values among the two groups (P= 0.41). There was no significant difference between uric acid levels among the two groups (P= 0.46). There was a significant correlation between the uric acid values among patients and healthy volunteers and PAB values (P <0.01). There was a significant correlation between the TG, values among patients and healthy volunteers and PAB values (P<0.05).Conclusion: This study showed oxidative stress could be used as a significant risk predictor in the coronary artery disease patient